PENGELOLAAN PEMBELAJARANMEMBACA PERMULAAN TULISAN BRAILLE MELALUI SISTEM MANGOLD PADA SISWA TUNANETRA - Tri Maryatun (Manajer Pendididikan, 2016)
This study aims to know learning management to read braille, for blind student in the class A. D1 SLB 16 Arga Makmur using mangold system. This study used two types of data, namely quantitative data (data of learning outcomes) and qualitative data (data informative of learning situation). The results of the study showed that learning with mangold system can improve the early ability to read braille for blind students in the class A. D1 SLB 16 Arga Makmur Students can reach KKM with a percentage of 70% which in successfully possition in the range of 70-80%.Keywords: reading braille, blind, mangold system